Bahasa Indonesia Kekinian: Pergeseran dan Kreativitas Pembentukan Kata Melalui Akronim, Blending, dan Kliping di Media Sosial - Maela Nikmatul Zuroh; Muhammad Hasbullah Ridwan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The rise of social media has influenced the use of Indonesian, particularly through the emergence of new vocabulary among the younger generation. This study aims to identify word-formation processes—specifically acronyms, blending, and clipping—in contemporary Indonesian used on social media and to describe their impact on the language's evolution in the digital era. Employing a qualitative descriptive method, the study draws data from posts, captions, and comments on TikTok and Instagram between January and May 2026. Data were collected using